2018
DOI: 10.1080/08037051.2018.1521263
|View full text |Cite
|
Sign up to set email alerts
|

LDL cholesterol is associated with systemic vascular resistance and wave reflection in subjects naive to cardiovascular drugs

Abstract: Background and aim: Low density lipoprotein cholesterol (LDL-C) is a primary risk factor for atherosclerosis, but it is also associated with elevated blood pressure (BP) and future development of hypertension. We examined the relationship between LDL-C and haemodynamic variables in normotensive and never-treated hypertensive subjects. Methods: We recruited 615 volunteers (19-72 years) without lipid-lowering and BP-lowering medication. Supine haemodynamics were recorded using continuous radial pulse wave analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 50 publications
6
15
0
Order By: Relevance
“…Although some reports have associated triglycerides and HDL-C with arterial stiffness [14][15][16], all studies do not support this finding [38][39][40]. Moreover, the association of LDL-C with arterial stiffness has been surprisingly weak in the published literature [12,13]. Therefore, our goal was to assess the association between AIP and functional cardiovascular variables using non-invasive recordings of haemodynamics.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Although some reports have associated triglycerides and HDL-C with arterial stiffness [14][15][16], all studies do not support this finding [38][39][40]. Moreover, the association of LDL-C with arterial stiffness has been surprisingly weak in the published literature [12,13]. Therefore, our goal was to assess the association between AIP and functional cardiovascular variables using non-invasive recordings of haemodynamics.…”
Section: Discussionmentioning
confidence: 93%
“…In spite of the dominant role of LDL-C in atherosclerosis, the relationship of LDL-C with PWV is rather weak [12]. Recently, we found that LDL-C was not associated with PWV when the level of BP was taken into account [13], and this finding is concordant with the majority of published papers [12]. High triglycerides concentration in 11,640 and 1,447 subjects, and low HDL-C levels in 15,302 subjects, were associated with increased PWV [14][15][16].…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations